Peningkatan Aktivitas dan Hasil Belajar Bahasa Inggris pada Siswa Kelas XPK 2 Madrasah Aliyah Negeri (MAN) 2 Pesisir Selatan Tahun Ajaran 2020/2021 melalui Pelaksanaan Model Pembelajaran Group Investigation - Risna Aris (Departement of Mathematics Education, 2023)
This study aims to determine the activities and learning outcomes of class X PK 2 MAN 2 Pesisir Selatan through the implementation of the Group Investigation learning model in English subjects. This type of research uses classroom action research. This research is reflective in nature by increasing classroom learning in a more professional manner. The subjects in this study were 33 students of class XPK 2. Implementation of this study using the